2013
DOI: 10.1097/iop.0b013e3182696592
|View full text |Cite
|
Sign up to set email alerts
|

Inferomedial Dermolipoma With Ectopic Lacrimal Gland

Abstract: A 25-year-old woman presented with a painless inferomedial subconjunctival mass in the right eye. The growth had been present since birth and had been increasing in size for over 1 year. Incisional biopsy with debulking proved the lesion to be a dermolipoma extending behind the globe that contained ectopic lacrimal gland tissue. The authors describe a very rare case of a complex dermolipoma arising in an atypical location and containing ectopic lacrimal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Complex choristomas with ectopic lacrimal gland have been noted to have a predisposition to bulbar conjunctiva and cornea, although it has been reported from eyelids, orbits and intraocular tissues such as ciliary body and iris 1, 2, 3, 4, 5. Numerous theories have been proposed to explain the occurrence of choristomas and ectopic lacrimal gland and include aberrant implantation of embryonic cells destined to differentiate into lacrimal gland and aberrations during closure of fissures and sutures 5…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Complex choristomas with ectopic lacrimal gland have been noted to have a predisposition to bulbar conjunctiva and cornea, although it has been reported from eyelids, orbits and intraocular tissues such as ciliary body and iris 1, 2, 3, 4, 5. Numerous theories have been proposed to explain the occurrence of choristomas and ectopic lacrimal gland and include aberrant implantation of embryonic cells destined to differentiate into lacrimal gland and aberrations during closure of fissures and sutures 5…”
Section: Discussionmentioning
confidence: 99%
“…Only two of the 61 cases were correctly diagnosed preoperatively. Ferri et al 2 reported a case of an inferomedial subconjunctival dermolipoma with ectopic lacrimal gland and concluded that the location was quite atypical based on the literature review. Verb et al 4 described a phakomatous choristoma presented as a lower eyelid mass with a mechanical nasolacrimal duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dermolipomas located in other quadrants are rare. As for the inferonasal quadrant, there have been only three reported cases of inferonasal dermolipoma published in the literature [ 5 - 7 ]. This is not the typical location for dermolipomas, hence emphasizing the unusual presentation of this case.…”
Section: Introductionmentioning
confidence: 99%